New records of amphibians and reptiles from Tlaxcala, México - Fernández, Jesús A.; Sánchez, Oscar; Flores-Villela, Oscar A. (Instituto de Ecología, A.C., 2006)
Tlaxcala is the smallest state of Mexico. There are not much studies of his herpetofauna. Like results of our work in the field during 2002-2003, we have reported nine new records of amphibian and reptiles.